2015
DOI: 10.1186/s12885-015-1929-y
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Bcl-2 inhibitor Obatoclax is a potent late stage autophagy inhibitor in colorectal cancer cells independent of canonical autophagy signaling

Abstract: BackgroundColorectal cancer is the third most common malignancy in humans and novel therapeutic approaches are urgently needed. Autophagy is an evolutionarily highly conserved cellular process by which cells collect unnecessary organelles or misfolded proteins and subsequently degrade them in vesicular structures in order to refuel cells with energy. Dysregulation of the complex autophagy signaling network has been shown to contribute to the onset and progression of cancer in various models. The Bcl-2 family o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 66 publications
3
27
0
Order By: Relevance
“…Cell lysis, SDS-page and Western blotting were performed according to standard procedures as described previously [45]. The following antibodies were used: anti-Beclin-1 (Santa Cruz Biotechnology, Heidelberg In order to quantify protein expression, we used ImageJ ® (by Wayne Rasband at NIH, Bethesda, MD, USA) for densitometric analysis as described previously [49]. In brief, band density was measured relative to the untreated control and then adjusted to tubulin as loading control.…”
Section: Protein Isolation Sds-page Densitometry and Western Blot Amentioning
confidence: 99%
“…Cell lysis, SDS-page and Western blotting were performed according to standard procedures as described previously [45]. The following antibodies were used: anti-Beclin-1 (Santa Cruz Biotechnology, Heidelberg In order to quantify protein expression, we used ImageJ ® (by Wayne Rasband at NIH, Bethesda, MD, USA) for densitometric analysis as described previously [49]. In brief, band density was measured relative to the untreated control and then adjusted to tubulin as loading control.…”
Section: Protein Isolation Sds-page Densitometry and Western Blot Amentioning
confidence: 99%
“…The Bcl-2 inhibitor ABT-737 has been identified as an autophagy inhibitor (Yang et al, 2016). Moreover, obatoclax which exhibits pan-Bcl-2 inhibition effect has been demonstrated to cause a striking inhibition of autophagy at late-stage in colorectal cancer and bladder cancer cells (Huang and Sinicrope, 2010;Koehler et al, 2015;Jiménez-Guerrero et al, 2018). Clarithromycin is a macrolide antibiotic frequently utilized in the treatment of upper and lower respiratory tract infections and Helicobacter pylori that has demonstrated inhibitory effects on autophagy (Altman and Platanias, 2012;Giulia Petroni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, multikinase inhibitor BAY 43-9006 that downregulates Mcl-1 through inhibition of translation (Rahmani et al 2005) or proteasomal degradation (Yu et al 2005) was shown to downregulate Mcl-1 also in HT29 cells (Yu et al 2005). Unlike ABT-737, pan-Bcl-2 inhibitor Obatoclax that binds to Bcl-2, Bcl-X L , Bcl-w and Mcl-1 (Konopleva et al 2008) was shown to be a potent late stage autophagy inhibitor in HT29 cells, causing cell growth arrest and cell death (Koehler et al 2015).…”
Section: Discussionmentioning
confidence: 99%